Knowledge Regarding Delirium Among Nurses of Selected Hospital of Bagmati Province, Nepal - Gurung, Manoj; Shrestha, Anukala; Shrestha, Moti Kumar; Adhikari, Pramod (NPRC Journal of Multidisciplinary Research, 2026)
Background: Delirium is common problem and reversible state among patient which may arise from prolong hospital stay, strenuous procedure, disrupted circadian rhythm, underlying medical condition and Hospital environment itself while recognizing and diagnosing delirium is a challenging process primarily reliant on the patient’s symptom profile. The studies from across the world shown that nurses’ knowledge regarding delirium is inadequate. This study is one of the very few Nepali addressing this issue. So, this study is aimed to find out the knowledge regarding Delirium among Nurses of Selected hospital of Bagmati Province, Nepal. Methodology: A Descriptive cross-sectional study design was used to conducted among 70 nurses of Green City Hospital, Kathmandu, Nepal by using non-probability convenient sampling technique. Data were collected using semi-structured questionnaire to assess the Socio- demographic data and level of Knowledge on Delirium. The Collected data were entered in SPSS software version 20 and analyzed by using descriptive statistics such as frequency, percentage mean and standard deviations and inferential statistics (Chi square) was used for measuring association between selected independent variables with level of knowledge then it is presented in tables. Result: The study findings reveals that more than half of the respondents (67.1%) had high knowledge, one third of the respondents (32.9%) had moderate level of knowledge regarding Delirium. There is statistically significant association between the level of knowledge regarding Delirium and education level (p=0.039) and practicing area (p=0.016) at 0.05 (Chi Square ’P’ Value) Conclusion: This study concludes that more than half of the respondents had high level of knowledge. However, one third of the respondents had moderate level of knowledge regarding Delirium. To make all nurses knowledgeable, they could be trained through the in-service education programs specifically on Delirium.